Optimizing the energy storage performance of K2O–Nb2O5–SiO2 based glass-ceramics with excellent temperature stability. Issue 7 (1st April 2021) - Du, Xinyi; Pu, Yongping; Li, Xin; Peng, Xin; Sun, Zixiong; Zhang, Jinbo; Ji, Jiamin; Li, Run; Zhang, Qianwen; Chen, Min
Abstract: Glass-ceramics possessing high power density, energy density and fast charge-discharge rate during a wide temperature range are considered to be the ideal materials for pulse power applications. Under the premise of negligible effect on the glass network structure, the energy storage performance was improved by introducing Na + ions, which reduced the carrier mobility and the conductivity in this study. The potassium sodium niobate silicate initial glass were synthesized by the traditional melting method, and the glass-ceramics were prepared by the crystallization treatment at 800 °C for 2 h. Introducing sodium ions promoted the formation of Na0.35 K0.65 NbO3 phase, and increased the permittivity to 104 simultaneously. Superior high breakdown strength (750 kV/cm) was obtained because of the competition between two physical mechanisms of electrical conductivity and micromorphology. When the sodium oxide content was 0.375, the discharge energy density of 2.44 J/cm 3 and high energy storage efficiency of 93% were obtained. Compared with ceramics, polymers and other niobate-based glass-ceramics reported currently, this work had achieved high actual discharge energy density (0.156 J/cm 3 ) and high power density (19.6 MW/cm 3 ) under low field strength, and had an extremely fast discharge rate (~14 ns) and excellent wide temperature stability (20–120 °C).